A drug-eluting nanofibrous hyaluronic acid-keratin mat for diabetic wound dressing - EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2022, Qatar University and Springer Nature Switzerland AG.Diabetes mellitus is a chronic metabolic disease associated with long-term multisystem complications, among which are non-healing diabetic foot ulcers (DFUs). Electrospinning is a sophisticated technique for the preparation of polymeric nanofibers impregnated with drugs for wound healing, burns, and diabetic ulcers. This study describes the fabrication and characterization of a novel drug-eluting dressing made of core–shell structured hyaluronic acid (HA)–keratin (KR)-polyethylene oxide (PEO) and polycaprolactone (PCL) nanofibers to treat diabetic wounds. The core–shell nanofibers produced by the emulsion electrospinning technique provide loading of metformin hydrochloride (MH), HA, and KR in the core of nanofibers, which in return improves the sustained long term release of the drug and prolongs the bioactivity. Morphological and chemical properties of the fibers were examined by SEM, FTIR, and XRD studies. It was observed that the fibers which contain HA and KR showed thin fiber structure, greater swelling capacity, fast degradation and increased cumulative drug release amount than neat emulsion fibers due to the hydrophilic nature of HA and KR. MH showed a sustained release from all fiber samples over 20 days and followed the first-order and Higuchi model kinetics and Fickian diffusion mechanism according to kinetic analysis results. In vitro cell culture studies showed that the developed mats exhibited enhanced biocompatibility performance with HA and KR incorporation. The results show that HA and KR-based emulsion electrospun fiber mats are potentially useful new nanofiber-based biomaterials in their use as drug carriers to treat diabetic wounds.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ÇEVRE; ENERJİ VE YAKITLAR; MALZEME BİLİMİ, BİYOMATERYAL; MALZEME BİLİMİ, SERAMİK; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, ENVIRONMENTAL; ENERGY & FUELS; MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE, CERAMICS; Seramik ve Kompozitler; Fizik Bilimleri; Biyomalzemeler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Atık Yönetimi ve Bertarafı; Ceramics and Composites; Physical Sciences; Biomaterials; Renewable Energy, Sustainability and the Environment; Waste Management and Disposal; Drug release; Emulsion electrospinning; Metformin hydrochloride; Natural polymers; Wound healing